An asymmetrical approach to understanding configurations of customer loyalty in the airline industry. (September 2017) - Prentice, Catherine; Correia Loureiro, Sandra Maria
Abstract: This study employs fuzzy set qualitative comparative analysis (fsQCA) to examine asymmetrical relationships among service attributes, relationship quality, and customer loyalty in the airline industry. The study incorporates customers' demographics and psychological variables to model customer loyalty. Customer loyalty is operationalised as behavioural and attitudinal dimensions in order to capture customers' actual behaviours and behavioural intentions. Symmetrical testing is also used to compare findings with those from fsQCA application. The study provides various causal recipes or configurations for predicting relationship quality and customer loyalty. The comparison between symmetrical and asymmetrical findings presents deeper and more insightful information. These findings provide useful guidelines and references for the relevant researchers and practitioners. The study also contributes to the literature by utilising symmetrical and asymmetrical tools to advance understanding of antecedent conditions of relationship quality and customer loyalty.